Host range and molecular and ultrastructural analyses of Asparagus virus 1 pathotypes isolated from garden asparagus Asparagus officinalis L. - Lantos, Edit; Krämer, Reiner; Richert-Pöggeler, Katja R.; Maiss, Edgar; König, Janine; Nothnagel, Thomas (Frontiers in Plant Science, 2023)
Asparagus samples were examined from growing areas of Germany and selected European as well as American countries. Overall 474 samples were analyzed for Asparagus virus 1 (AV1) using DAS-ELISA. In our survey, 19 AV1 isolates were further characterized. Experimental transmission to 11 species belonging to Aizoaceae, Amarantaceae, Asparagaceae and Solanaceae succeeded. The ultrastructure of AV1 infection in asparagus has been revealed and has been compared with the one in indicator plants. The cylindrical inclusion protein (CI), a core factor in viral replication, localized within the cytoplasm and in systemic infections adjacent to plasmodesmata. The majority of isolates referred to pathotype I (PI). These triggered a hypersensitive resistance in inoculated leaves of Chenopodium spp. and were incapable to infect Nicotiana spp. Only PII and PIII infected N. benthamiana systemically but differed in their virulence when transmitted to Chenopodium spp. The newly identified PIII generated amorphous inclusion bodies and degraded chloroplasts during systemic infection but not in local lesions of infected Chenopodium spp. PIII probably evolved via recombination in asparagus carrying a mixed infection by PI and PII. Phylogeny of the coat protein region recognized two clusters, which did not overlap with the CI-associated grouping of pathotypes. These results provide evidence for ongoing modular evolution of AV1.